Analytic Network Process (Anp) And Benefit Cost Opportunity Risk (Bcor) Approach For Selecting Sustainable Water Quality Management Strategies - Teguh Bayu Aji Dwi Driyatmoko; Udisubakti Ciptomulyono (Publikasi Indonesia, 2025)
Water resource management faces complex challenges in decision-making, particularly in selecting effective strategies to restore polluted river water quality. Kali Surabaya, as a strategic water source, has experienced quality deterioration due to domestic and industrial pollution, compounded by climate change pressures. Recent assessments indicate mild pollution with several parameters not meeting quality standards. Given resource constraints and rising demands for class I and II raw water, a systematic approach is necessary to determine the optimal recovery strategies. This study employs the Analytic Network Process (ANP) method integrated with the Benefit, Cost, Opportunity, and Risk (BCOR) framework to evaluate interrelated criteria and sub-criteria, identifying strategic priorities specifically in the Kali Tengah segment, which faces considerable pollution pressure. Based on literature review, water quality data, and expert questionnaire results, the primary criteria identified for strategy selection show Benefit (0.4127) as the highest priority, followed by Opportunity (0.23118), Cost (0.1292), and Risk (0.0695). The recommended strategies with optimistic scenario values include establishing communal industrial wastewater treatment (10.8102), applying nanobubble technology (0.6534), and periodic flushing (0.1396). Considering sustainability aspects (economic, social & environmental), this integrated approach aims to enhance long-term water quality management efforts